Analisis Waste Proses Pembangunan Perumahan Sederhana (Low Cost Housing) Menggunakan Root Cause Analysis (RCA) - Nurlaelah Nurlaelah (IKRAITH-Teknologi, 2022)
The existing condition of the house construction process in low-cost housing (LowCost Housing) still has waste constraints, including waste Overproduction,Inventory, Defect, Motion, Transportation, Processing and Waiting). Waste resultsin delays in the completion of housing construction for consumers.To overcome the waste problem, identification and analysis of the root causes ofwaste is carried out using the Root Cause Analysis (RCA) method. The results ofthe RCA analysis show that the funding factor (Money) and the human factor (Man)are the 2 (two) root causes of the waste of the house construction process in lowcosthousing.